(untitled) (Research, Society and Development, 2023)
Nowadays, paving is something fundamental for society, facilitating the transport of goods, and providing an agile and fast displacement in urban roads. As a result, several researchers, engineers and specialists in the area of ​​the environment are looking for ways to make these roads more attractive, bringing less risk to the environment and public health, since asphalt is a product acquired by various combinations of substances, where it produces a huge amount of carbon, generating great consequences for the population and nature. The objective of this work is to use sunflower oil combined with the asphalt binder, seeking to generate less environmental impacts, hide air pollution, satisfy toxic inhalation, normally the paving, made of petroleum, emits a severe amount of polluting particles when exposed to high temperatures, sunlight and rain. The methodology has analytical, descriptive and experimental conditions, following the resistance test, fatigue test and macrostructural analysis, based on NBR 9781 (2013). Results: In general, sunflower oil resists high temperatures, provides more durability, and becomes a more effective alternative, with vehicle fuel savings, electricity savings and less waste generation, efficient physical properties and Asphalt chemicals reduce CO² emissions and reduce long-term maintenance and repair costs, making it a promising and defensible alternative to paving.